Pemanfaatan Media Digital Berbasis Canva Dalam Pembelajaran Sejarah - Badrudin Badrudin (Program Studi Pendidikan Sejarah, Universitas Setiabudhi Rangkasbitung, 2023)
Effective history learning requires an innovative approach and the use of very interesting media to increase students' interest and understanding. Digital technology, including the Canva application, can be an effective tool for creating interesting and interactive learning media. This research aims to explain the use of Canva-based digital media in history learning, as well as its impact on student interest and understanding.